2022
DOI: 10.52711/2231-5691.2022.00026
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Cleaning Validation-Regulatory Guidelines for The Pharmaceutical Industry

Abstract: Manufacturing of Pharmaceutical products shall demonstrate a control to reproduce consistently the desired quality of product, wherein the control of cross-contamination plays an important role. An effective cleaning shall be in place to provide documented evidence that the cleaning methods employed within a facility consistently controls potential carryover of product (including intermediates and impurities), cleaning agents and extraneous material into subsequent product to a level which is below predetermin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In feed manufacturing, carryover can occur in a single piece of equipment, multiple pieces, or the entire production line [13]. The phenomenon also occurs in the human food and pharmaceutical industries [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In feed manufacturing, carryover can occur in a single piece of equipment, multiple pieces, or the entire production line [13]. The phenomenon also occurs in the human food and pharmaceutical industries [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…A good manufacturing practice (GMP) is essential to prevent contamination of pharmaceutical products and starting materials. It has been demonstrated that pharmaceutical products are susceptible to contamination from a variety of contaminants, including microorganisms, past products (including active pharmaceutical ingredients and excipients), residues of cleaning agents, dust, particulates and lubricants, as well as dust from previous products [1]. Contamination and cross-contamination can be prevented by ensuring that adequate cleaning procedures are followed properly.…”
Section: Introductionmentioning
confidence: 99%